2022
DOI: 10.1186/s40249-022-01007-6
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox claims new victims: the outbreak in men who have sex with men

Abstract: Monkeypox has a very prominent regional epidemic. It has been confined to Western and Central African countries. Sporadic cases found in countries outside Africa generally have a history of sojourn in endemic areas. However, the recent multinational outbreak of monkeypox cases in Europe in early May 2022 has revealed a changing epidemiological trend, those confirmed cases had no sojourn history in endemic areas and with a high proportion of cases involving men who have sex with men (MSM). Among the MSM cases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 7 publications
1
48
0
6
Order By: Relevance
“…In Italy, the number of cases increased during the last week of July [ 22 ]. This recent multinational outbreak of Monkeypox cases has revealed a changing epidemiological trend, with a high proportion of cases occurring among MSM, reaching 87% in Spain [ 28 , 29 ]. Of the eight male patients described in the present study, six (75%) were MSM.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the number of cases increased during the last week of July [ 22 ]. This recent multinational outbreak of Monkeypox cases has revealed a changing epidemiological trend, with a high proportion of cases occurring among MSM, reaching 87% in Spain [ 28 , 29 ]. Of the eight male patients described in the present study, six (75%) were MSM.…”
Section: Discussionmentioning
confidence: 99%
“…The basic reproductive number (R0) was higher than 1 in MSM (Men who have Sex with Men) populations and lower than 1 in other populations, as estimated by mathematical models. R0 was estimated to be 1.8 in Spain, 1.6 in the UK, and 1.4 in Portugal ( 18 ). At present, there were no confirmed human monkeypox patients in mainland China in 2022, which may be due to the government's strict new crown entry quarantine measures and the active promotion of human monkeypox prevention and control knowledge to the public.…”
Section: Discussionmentioning
confidence: 99%
“…Immunodeficiency may lead to worse clinical outcomes of a monkeypox infection (10). Liu et al (11) suggested that an advanced or poorly virally controlled HIV infection may lead to more severe outcomes after monkeypox infection. According to Thornhill et al…”
Section: Vaccine Stockpile and Vaccinationmentioning
confidence: 99%